Pursuing excellence : a values-based, systems approach to help companies become more resilient - Strobel, Brian (Boca Raton, FL : Routledge, 2021)
This book is for the people who lead our companies. Our world suffered a staggering blow. We will recover. Many of our companies are still suffering. Some of them will not recover. We're in a time of disruption. A company's culture will play a big part in managing through this disruption. Senior leaders must establish a clear purpose, a strong set of core values, and a plan to translate strategy into action. Companies will be seeking to transform, to become more efficient and resilient. Most attempts to do so fail. They fail because we try to solve the wrong problem with the wrong system. We attempt to change the way people act. But to achieve sustained improvement, we must focus on changing the way they think. Over the last thirty years, we've experimented with Lean, Six Sigma, and other improvement initiatives. Each failed to move beyond average performance and sustain transformational improvement. Average then became a learned behavior. To move forward, we must unlearn some things. We must change our problem definition and our defined systems. And we can do this by framing the problem through the lens of Operational Excellence.
Part I: Things that are and that Could be -- Chapter 1 Start with the Beginning but Focus on the End -- Part II: Things we don't See -- Chapter 2 Validating Our Values and Beliefs -- Chapter 3 Honing Our Culture -- Chapter 4 Clarifying Our Leadership -- Chapter 5 Aligning Our Strategy -- Chapter 6 Integrating Our Systems and Structures -- Chapter 7 Understanding Our Marketspace -- Part III: Things we do See -- Chapter 8 Engaging Our People -- Chapter 9 Improving Our Processes -- Chapter 10 Realizing Our Products -- Part IV: Things the Customer Sees -- Chapter 11 Optimizing the Customer Experience -- Part V: Why these Things Matter -- Chapter 12 Application
"a Productivity Press book"
OCLC-licensed vendor bibliographic record.
Keywords: Organizational change; Organizational effectiveness; Organizational behavior; BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Workplace Culture